Palladas, Constantine, and Christianity - Woods, David (The journal of theological studies, 2016)
It has recently been argued that the epigrammatist Palladas of Alexandria wrote during the late reign of Constantine I, and that several of his poems support the evidence of Eusebius of Caesarea in his Vita Constantini concerning the character and policy of Constantine I as a firmly committed Christian, deeply hostile to traditional religion. In this essay, I re-examine the evidence of five poems (A.P. 9.378, 528; 10.90; 11.281, 386) in order to demonstrate that Palladas was much more hostile to Constantine than has previously been recognized, and that he preserves important evidence for the early development of several important anti-Constantinian themes within later pagan historiography.